Pemberdayaan Masyarakat Pesisir Melalui Hilirisasi Produk Perikanan dan Penguatan Usaha Agribisnis di Gampong Punge Jurong - Nuzulul Fahmi; Julia; Hamdani; Ibnu Yassier; Al Asri Abubakar; Budi Alhadi; Safrika (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2026)
This Community Service initiative aims to enhance the capacity of the coastal community in Gampong Punge Jurong through the downstream processing of fishery products and strengthening of agribusiness ventures. The challenges addressed include low value-added in fishery products, limited processing skills, weak business management, and suboptimal digital marketing. The program was implemented using a participatory approach involving outreach, training, demonstrations, and community mentoring. Activities focused on processing fishery products into value-added items—such as kemamah (traditional dried tuna) and fish meal—as well as training in packaging, business management, and digital marketing. The results indicate an improvement in the community's knowledge, skills, and motivation to develop fishery-based businesses. Collaboration between the Agribusiness Study Program at Jabal Ghafur University and the Agricultural Engineering Study Program at Syiah Kuala University facilitated technology transfer and community capacity building. The program fosters product diversification, increases the value-added of fishery products, and creates opportunities for income growth. Sustaining the program requires continued mentoring, institutional strengthening, product quality improvement, and the expansion of marketing networks.